Ethical Criteria to Review Research in Social Sciences. Systematization of an Experience [Criterios Éticos Para Revisar Investigaciones en Ciencias Sociales. Sistematización de Una Experiencia] - Villalta-Paucar, M (Univ Nacional de Educacion a Distancia (UNED), 2022)
The evaluation criteria used by the Research Ethics Committees come from studies in medicine, some specialists project, from their sources and experiences, universal ethical requirements based on clinical research. This opens the discussion on whether such principles can be transferable to evaluate social science research, which commonly uses complex methodologies and knowledge that challenge the Committees on ways to understand informed consent, the risks and benefits of research. The objective of the article is to systematize the project review work of the Institutional Ethics Committee (IEC) of the University of Santiago, Chile. The methodology includes the content analysis of 114 projects from the social sciences. The seven universal ethical requirements of Ezekiel Emanuel were used as a guiding element of the analysis, whose proposal is assumed and followed by Chilean ministerial instructions that order the work of the Research Ethics Committees. Among the results is that the universal requirements of Emanuel are present in a large part of the projects in social sciences, but they are not enough to approach the specific situations of research in social sciences, being the deliberation of the investigations by multidisciplinary teams essential to respect the heterogeneity and complexity of the social subject. © 2022 Universidad Nacional de Educacion a Distancia. All rights reserved.